TYK 2 inhibitors for the treatment of dermatologic conditions: the evolution of JAK inhibitors. (30th April 2021) - Jo, Christine E.; Gooderham, Melinda; Beecker, Jennifer
Abstract: Increasing understanding of cytokines as major drivers of immune‐mediated diseases has revolutionized targeted treatments for these conditions. As the pathogenesis of autoimmune conditions is mediated by a complex interplay of various cytokines, Janus kinase (JAK) inhibitors have been of particular interest due to their ability to target multiple cytokines simultaneously. However, due to safety concerns with first generation JAK inhibitors, most notably from JAK2 and JAK3 inhibition, interest has shifted to more selective inhibition of TYK2. Three key TYK2 inhibitors that have advanced furthest in clinical trials for treatment of dermatologic autoimmune conditions are deucravacitinib (BMS‐986165), brepocitinib (PF‐06700841), and PF‐06826647. This review outlines the current understanding of the efficacy and safety of these three TYK2 inhibitors from completed phase I and II studies and summarizes studies currently in progress for dermatologic conditions.